FRI0271 Final Evidence-Based Recommendations for Diagnosis and Treatment of Paediatric Vasculitides. (9th June 2015) - De Graeff, N.; Groot, N.; Kamphuis, S.; Avcin, T.; Bader-Meunier, B.; Dolezalova, P.; Kone-Paut, I.; Lahdenne, P.; McCann, L.; Pilkington, C.; Ravelli, A.; Van Royen, A.; et al.
Abstract : Background: The paediatric vasculitides are a group of rheumatic diseases characterized by blood vessel inflammation. Several vasculitic syndromes can be distinguished based on the size of the involved vessels as well as the specific symptoms. Incidence of these syndromes is low and evidence-based paediatric guidelines are lacking. SHARE (Single Hub and Access point for paediatric Rheumatology in Europe) is a project that aims to develop European evidence-based guidelines for diagnosis and treatment of these and other rare paediatric rheumatic diseases (PRD). Objectives: To develop evidence-based recommendations for diagnosis and treatment of paediatric vasculitides, i.e. Kawasaki Disease (KD), Henoch Schönlein Purpura (HSP), Polyarteritis Nodosa (PAN), Granulomatosis with Polyangiitis (GPA), Eosinophilic granulomatosis with Polyangiitis (EGPA) and Takayasu's Arteritis (TA). Methods: A systematic review of literature was conducted (results presented at PReS 2014), from which evidence-based recommendations were derived. A European expert committee evaluated these recommendations, both by online surveys and by discussion using the nominal group technique 1 during several in-person consensus meetings in Genoa (Italy, March '14, results presented at PReS 2014), Utrecht (the Netherlands, January '15) and Barcelona (Spain, March '15). Recommendations were accepted for the final guidelines if more than 80% agreement was reached. Results: Evidence from literature and expert opinion led to the formulation of recommendations for the different paediatric vasculitides. Adding to the 44 statements accepted with more than 80% consensus in Genoa, an additional 78 statements were accepted in Utrecht. Included statements ranged across different topics, including criteria for diagnosis, referral indications, clinical and laboratory parameters, imaging and treatment of the different vasculitic syndromes. Statements for discussion in Barcelona will focus on general and interdisciplinary aspects of care for children with vasculitis and other PRDs. Conclusions: SHARE aims to provide minimal standards of care for PRD. We present the final recommendations for diagnosis and treatment of paediatric vasculitides. These recommendations will contribute to a more uniform and evidence-based foundation for diagnosis and treatment of KD, HSP, PAN, GPA, EGPA and TA in children. References: Harvey N, Holmes CA. Nominal group technique: an effective method for obtaining group consensus. Int J Nurs Pract. 2012; 18:188-94 Acknowledgements: This project is supported by a grant from European Agency for Health and Consumers (EAHC), grant number 2011 1202. Disclosure of Interest: None declared